Childhood Adversity and Adolescent Anxiety: The Role of Intolerance of Uncertainty as a Mediator - Viteri, Camila; Mokoena, Thandiwe (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the mediating role of intolerance of uncertainty (IU) in the relationship between childhood adversity and adolescent anxiety. Methods and Materials: A descriptive correlational design was used with a sample of 392 adolescents (aged 13–18) from South Africa, selected based on the Krejcie and Morgan sample size table. Standardized instruments were employed to measure variables: the Childhood Trauma Questionnaire (CTQ) for childhood adversity, the Intolerance of Uncertainty Scale–12 (IUS-12) for IU, and the Screen for Child Anxiety Related Emotional Disorders (SCARED) for anxiety symptoms. Data were analyzed using SPSS-27 for descriptive and Pearson correlation analyses, and AMOS-21 for Structural Equation Modeling (SEM). The model fit was assessed using indices such as Chi-square, CFI, TLI, GFI, and RMSEA. Findings: Descriptive statistics indicated moderate to high levels of childhood adversity (M = 67.42), IU (M = 34.78), and adolescent anxiety (M = 42.15). Pearson correlations revealed significant positive relationships among all variables (e.g., adversity and anxiety: r = .52, p < .001). The SEM analysis showed that IU significantly mediated the relationship between childhood adversity and adolescent anxiety. Specifically, childhood adversity predicted IU (β = .48, p < .001), IU predicted anxiety (β = .51, p < .001), and the indirect effect of adversity on anxiety through IU was also significant (β = .24, p < .001), supporting a partial mediation model with a good overall fit (e.g., CFI = 0.96, RMSEA = 0.058). Conclusion: The findings highlight IU as a key cognitive mechanism linking early adverse experiences to anxiety symptoms in adolescence. Addressing IU through targeted interventions may help mitigate anxiety in adolescents with a history of childhood adversity.